Pendidikan Nilai Berbasis Keluarga, Sekolah, dan Masyarakat - Sulthoni (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2016)
Planting values needs to be balanced with a supportive environment. Value education is not only a school task, but all parties, be it family, school, community or government. Families need to understand the values given at school to support family life. In today's society, values are still lacking as a result of economic pressures, where parents are busy thinking about fulfilling their daily needs. This can be an obstacle to the development of children's values.